Spermatozoa with numerical chromosomal abnormalities are more prone to be retained by Annexin V‐MACS columns. (14th June 2017) - Esbert, M.; Godo, A.; Soares, S. R.; Florensa, M.; Amorós, D.; Ballesteros, A.; Vidal, F.
Summary: Colloidal super‐paramagnetic microbeads conjugated with annexin V are effective for separating apoptotic spermatozoa by MACS as a result of the high affinity of annexin V for externalized PS molecules. The effectiveness of the procedure in reducing the percentage of sperm with fragmented DNA and abnormal morphology has also been reported. However, it is still unknown if it could decrease the percentage of aneuploid spermatozoa. The objective of our prospective study, performed on 16 males with abnormal FISH on spermatozoa, was to assess if MACS columns were useful tools to retain spermatozoa carrying chromosomal abnormalities in semen samples processed after density gradient centrifugation (DGC). The pellet obtained after DGC was subjected to MACS, and sperm FISH analyses were performed both in the eluded fraction and in the fraction retained in the column. The observed frequencies of disomy and nullisomy 13, 18, and 21, X and Y, as well as the diploidy rates in the MACS eluded fraction and the fraction retained in the MACS column were recorded. We observed that the frequencies of aneuploidies in the eluded fraction were lower than in the fraction retained in the MACS column (0.59% vs. 0.75%; p = 0.010). DGC determined a significant reduction in sperm concentration ( z ‐ratio = 2.83; p = 0.005) and a significant increase in sperm progressive motility ( z ‐ratio = −3.5; p < 0.001). MACS also led to a significant reduction in sperm concentration ( z ‐ratio = 3.14; p = 0.002) and a significant increase in progressive motility ( z ‐ratio = −2.59; p = 0.01) when compared with the post‐DGC sample. Sperm concentration was similar in the two fractions generated by MACS ( z ‐ratio = 0.63; p = 0.52), while progressive motility was significantly higher in the MACS eluded fraction ( z ‐ratio = 2.42; p = 0.02). According to our results, MACS columns are able to selectively retain spermatozoa carrying chromosomal abnormalities. Furthermore, the performance of DGC and MACS on semen samples leads to an enrichment of progressive motility.